Anti-hyperglycemic and anti-hyperlipidemic effects of chia seed extract in alloxan-induced diabetic mice (Bangladesh Journal of Animal Science, 2024)
Diabetes is a chronic and debilitating metabolic disorder that gradually impairs the body's ability to regulate blood sugar levels, leading to complications that can affect multiple organs and systems, including the heart, kidneys, nerves, and eyes. Chia seed contains a high concentration of dietary fiber, omega-3 fatty acids, and essential amino acids, which may have hypotensive, hypoglycemic, and anticholesterolemic benefits. The objective of this research was to investigate whether administration of chia seed extract (CSE) may reduce the frequency of metabolic diseases in mice with or without diabetes. The experimental mice were divided into four groups such as normal control group, normal mice with 50 mg/ kg body weight of CSE, diabetic control group (no CSE) and diabetic mice with 50 mg/ kg body weight of CSE. In order to induce diabetes, 2% alloxan solution was used. The results showed that CSE administration led to a significant reduction in food intake in normal mice, but it did not exhibit a notable decrease in diabetic mice. While the extract did not affect the body weight of diabetic mice, a slight reduction was observed in the normal mice treated with chia. In comparison to the normal and diabetic mice, the blood glucose level was lower in chia-treated groups at all-time points of glucose tolerance test. Additionally, CSE showed a tendency to reduced LDL, TC, TG and HDL concentrations. Furthermore, CSE treated groups showed reduced liver and kidney weight in comparison to the normal and diabetic mice, but the weight of the heart was almost similar in all groups. The above findings suggest that CSE exhibits anti-hyperglycaemic, and lipid-lowering properties. These effects could potentially be used to reduce the risk of metabolic disorders and assist diabetic subjects in maintaining lipid and glucose homeostasis.Bangladesh Journal of Animal Science 53(4): 144-153, 2024